Policy Implementation In Promotion Employee Positionin The National Directorate Of Manpower (Human Resource)At The Ministry Of Justice In Timor Leste - Adriano Ildefonso Da Cruz (Jurnal Hukum Khaira Ummah, 2021)
The problems in this research, first: How is the policy implementation in the promotion of employee positions at the National Directorate of Manpower (Human Resource) at the Ministry of Justice in Timor Leste?Second,What are the factors that support and hinder the implementation of policies in the promotion of employee positions at the National Directorate of Manpower (Human Resource) at the Ministry of Justice in Timor Leste?Third,What is the strategy to overcome obstacles to policy implementation in the promotion of employee positions at the National Directorate of Manpower (Human Resource) at the Ministry of Justice in Timor Leste?This research is a researchsociological juridical.The results of the study conclude that the promotion of positions carried out at the National Directorate of Manpower/Human Resource (Directorate Nacional dos Recursos Humano/DNRH) is indeed in accordance with the needs of the institution but is more influenced by political factors, as well as a spoil system in which the appointed officials are an option. superiors who share the same political ideology with them and do not go through a transparent and accountable recruitment process as mandated by the applicable employment law.